DIGITIZATION OF THE ECONOMY OF UKRAINE AND E-COMMERCE AS ITS COMPONENT - KULAKOVA, Svitlana; ZHYTNYK, Oksana (Herald of Khmelnytskyi National University. Economic sciences, 2022)
Despite the gap between Ukraine and the European Union in the general development of the economy and various state institutions, our state is gradually approaching the advanced countries of Europe in terms of the prevalence and availability of digital web services. In the matter of finding out the main trends of Internet technologies, the annual reports of the Kepios company, whose founder is Simon Kemp, the chief analyst of DataReportal, are authoritative for international corporations. Another report called "DIGITAL 2022: UKRAINE" says that in January 2022 there were about 31.10 million Internet users in Ukraine. The level of Internet penetration at the beginning of the year was 71.8% of the total population. For comparison, this indicator is 93% in Germany, 93% in France, 98% in Switzerland, 88% in Romania, 87% in Poland, and 92% in the USA. However, even under the difficult economic and political conditions in which Ukraine currently finds itself, it has a large number of projects related to digitalization. At the same time, taking into account Ukraine's desire to become a member of the EU, European countries are promoting the use of digital technologies in the economy of our country in every possible way.So, in our time, the process of digitalization of the economy is gaining momentum. Based on the essence of the phenomenon of the digital economy, its formation is directly related to the modernization and application of information and communication technologies, for which the Internet and various gadgets are the basis.Thus, in the article, the authors describe digitization as a complex economic process of radical transformation of the economies of the world. At the same time, attention was drawn to EU initiatives aimed at the implementation of information technologies in the spheres of business and state management. The impact of the large-scale economic shocks that Ukraine has experienced in recent years on the e-commerce sphere was also considered.
Keywords: digitization; e-commerce; Internet; digital economy